Dynamical model of an obscuring clumpy torus in AGNs: I. velocity and velocity dispersion maps for interpretation of ALMA observations - Bannikova, Elena Yu; Sergeyev, A.V.; Akerman, N.A.; Berczik, Peter; Ishchenko, M.V.; Capaccioli, M.; Akhmetov, V.S. (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT. We have developed the dynamical model of a clumpy torus in an active galactic nucleus (AGN) and compared to recent The Atacama Large Millimeter Array